2016
DOI: 10.3892/mmr.2016.5439
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant plasmid containing CpG motifs as a novel vaccine adjuvant for immune protection against herpes simplex virus 2

Abstract: The aim of the present study was to evaluate the efficacy of a herpes simplex virus type 2 (HSV-2) DNA vaccine co‑immunized with a plasmid adjuvant containing CpG motifs. A novel eukaryotic expression plasmid vector containing kanamycin resistance gene (pcDNA3Kan) was acquired from pET‑28a(+) and pcDNA3 plasmids. A gene encoding full length HSV‑2 glycoprotein D (gD) was amplified from the pcDNA3‑gD plasmid, which was cloned into pcDNA3Kan resulting in the construction of the recombinant plasmid pcDNA3Kan‑gD (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Although this DNA vaccine has huge potential, it still needs to overcome a series of limitations and challenges. Low immunogenicity is a potential disadvantage; however, multiple types of adjuvants including cytokines, the granulocyte-macrophage colony-stimulating factor, the CpG oligodeoxynucleotide, etc., have been proven helpful for enhancing the immunogenicity of DNA vaccines [ 41 , 42 , 43 ]. Compared with viral vectors, DNA vaccine delivery systems are safer, but the risk of insertional mutagenesis stills exists [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this DNA vaccine has huge potential, it still needs to overcome a series of limitations and challenges. Low immunogenicity is a potential disadvantage; however, multiple types of adjuvants including cytokines, the granulocyte-macrophage colony-stimulating factor, the CpG oligodeoxynucleotide, etc., have been proven helpful for enhancing the immunogenicity of DNA vaccines [ 41 , 42 , 43 ]. Compared with viral vectors, DNA vaccine delivery systems are safer, but the risk of insertional mutagenesis stills exists [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid containing multiple CpG motifs have been reported to induce a Th 1 dominant cytokine profile and enhance antigen specific humoral immune response to viral antigens (Guo et al 2011, Luo et al 2012, He et al 2016. It has been reported that phosphorothioate CpG ODN triggers innate immune activation through the TLR9-mediated signaling pathway (Hemmi et al 2000, Kumagai et al 2008, Lange et al 2018), yet whether CpG motif enriched plasmid also stimulates the TLR9 signaling cascade is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also assessed the immunogenicity of DNA vaccines containing chemokine-expressing sequences for HIV-1 immunization [144][145][146]. The CpG oligodeoxynucleotide (ODN) is another common genetic adjuvant used for DNA vaccines [9,147,148]. Preclinical studies have demonstrated that CpG ODN activates TLR9-bearing B cells and plasmacytoid dendritic cells and further support the induction of strong Th1-type responses [149].…”
Section: Techniques To Overcome Immunogenic Issues Of Dna Vaccinesmentioning
confidence: 99%